Regression Testing Process for Small Organization for Quality Software - Joseph, Jasmin.; Anand, K.Vijay (IJRDO -Journal of Computer Science Engineering, 2016)
Software has been component of current society for more than 50 years. There are more than a few software development methodologies in use today. This paper addresses the study in the part of regression testing. Every time a system is altered regression tests have to be run to validate these changes. Its well prepared setup and support of its effecting is desired across small organizations developing software. The goal of this paper is to explain quality assurance and software testing domains. In this paper implementation is focused on small organizations, which develops commercial, off-the-shelf software. In this work problems are identified and information and best practices are provided to help such type of organizations with regression testing, and thereby with overall quality of their products.